Essential oil composition and antioxidant activity in Valeriana jatamansi Jones: influence of seasons and growing sources. Issue 1 (2nd January 2017) - Rawat, Sandeep; Jugran, Arun Kumar; Bhatt, Indra D.; Rawal, Ranbeer S.; Andola, Harish C.; Dhar, Uppeandra
Abstract: Valeriana jatamansi is a perennial medicinal herb used in traditional and modern medicines for preventing number of diseases. Root samples were collected from wild and cultivated conditions in different seasons (spring, summer and winter) and analyzed for essential oil composition using gas chromatography – Mass spectrometry (GC–MS). Antioxidant activity of essential oil was evaluated using DPPH (1, 1-Diphenyl-2-picrylhydrazyl radical) assay. A total of thirty compounds (constitutes 80.1–92.1% of total essential oil) were detected by GC–MS analysis. Patchouli alcohol (36.6–52.8%) was recorded as a major compound followed by guaiene epoxide (3.6–11.5%), seychellene (4.2–5.6%), α-guaiene (2.2–4.6%), kessane (2.7–3.6%), α-patchoulene (0.1–2.3%), β-selinene (0.8–3.1 β-acoradienol (0.6–2.4%), ar-curcumene (0.7–2.2%), γ-patchoulene (1.4–2.6%), viridiflorol (0.6–2.4%), and α-humulene (0.1–4.6%). Essential oil content was recorded higher during winter season in wild (0.9%) and cultivated plants (0.8%) as compared to other seasons. Antioxidant activity of essential oil measured by DPPH radical activity assay varied (IC50 = 117.5–227.6 μL/mL) among seasons and growing conditions. Winter season is recommended for maximum essential oil yield and spring season for antioxidant activity.